Pengaruh Bopo, Nim Dan Ldr Pada Profitabilitas Bank Negara Indonesia Periode 2005-2024 - Hardiyanto, Hardiyanto; Chandradoni, Dhimas; Fadilah, Ahmad Ridho; Ikbal, Maulana; Amzar, Fadillah; Sumantri, Fazhar (Jurnal Mirai Management, 2025)
This study aims to determine the impact of Operating Expenses on Operating Income (BOPO), Net Interest Mergin (NIM), and Loan to Deposit Ratio (LDR) on Return on Assets (ROA). This research uses quantitative methods and multiple linear regression analysis. The data this time is the catalog data of Bank Negara Indonesia during 2005-2024. In this study, the dependent variable is ROA while the independent variables are BOPO, NIM, and LDR. The fit of the BOPO multiple regression model is acceptable and LDR and NIM have decreased. The coefficient of determination gets a very high percentage. This means that the variation of ROA value can be explained by BOPO, NIM, and LDR variables very influential. The results of this hypothesis test can explain that the independent variables simultaneously have a significant influence on ROA. Partially, the BOPO and LDR variables have a negative and significant effect on ROA, the NIM variable has a positive and significant effect on ROA.